2006
DOI: 10.1007/s11046-006-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Allee Effect in the Infection Dynamics of the Entomopathogenic Fungus Beauveria bassiana (Bals) Vuill. on the Beetle, Mylabris pustulata

Abstract: Successful infection by Beauveria bassiana as with all other entomopathogenic fungi, is accomplished only at a high conidial dose while, theoretically, a single conidium should be sufficient. Indeed, this is a major deterrent in its use as a biocontrol agent. High pathogen load for infection is required by organisms which display 'Allee' effect. In such organisms, a threshold exists for pathogen dose, below which no infection can be caused. B. bassiana has a semelparous life cycle and, therefore, its infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Several studies have empirically documented dose-dependent establishment, incubation time, and host mortality for microparasites (Agnew and Koella 1999;McLean and Bostock 2000;Hughes et al 2004;Devi and Rao 2006), which are processes that may lead to a demographic Allee effect in the population dynamics of the parasite (Regoes et al 2002). Nonetheless, for macroparasites, we are unaware of empirical examples of Allee effects, including mate limitation or other effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have empirically documented dose-dependent establishment, incubation time, and host mortality for microparasites (Agnew and Koella 1999;McLean and Bostock 2000;Hughes et al 2004;Devi and Rao 2006), which are processes that may lead to a demographic Allee effect in the population dynamics of the parasite (Regoes et al 2002). Nonetheless, for macroparasites, we are unaware of empirical examples of Allee effects, including mate limitation or other effects.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent publications have shown that B. bassiana isolates are very genetically variable (Aquino de Muro et al 2003Estrada et al 2007;Ormond 2007), and concomittantly highly phenotypically variable in parameters such as virulence (Bidochka et al 2002;Devi and Rao 2006;Talaei-Hassanloui et al 2006). The natural enemy escape hypothesis is often used as an explanation for the rapid establishment and proliferation of an invasive alien species; the geographical displacement of the species results in escape from predators and parasites and so gives the invading species an advantage over native species that are attacked by a suite of indigenous natural enemies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Soil plays a key role in forming insect populations hence the inhabiting EPF. The communities of EPF differ from one location to another, for example, populations of EPF in the arable soils seem to be different than those in barren lands (Devi et al 2006;Garrido-Jurado et al 2011). Quesada-Moraga et al (2007 detected EPF populations in a wide area of Spain, the EPF were isolated from 175 soil samples out of the 244, and only 2 species were found, B. bassiana and M. anisopliae.…”
Section: Factors Affecting Epf Virulencementioning
confidence: 99%